Effect of Anisotropic Dust Pressure on the Formation and Propagation of Arbitrary Amplitude Dust Acoustic Solitary Waves (DASW) in a Magnetized Dust-Ion-Electron Plasma - Choudhury, Mamani (East European Journal of Physics, 2025)
Arbitrary amplitude dust acoustic solitary waves (DASW) in a dusty magneto-plasma with anisotropic dust pressure and nonthermal distribution of ions and electrons has been investigated. Sagdeev pseudopotential technique is used to derive an energy balance equation and to analyze various properties of dust acoustic solitons. The effects of anisotropic dust pressure, dust number density ratio, non-thermality, etc., are investigated numerically for the propagation of DASWs. It is found that rarefactive solitons can exist for negatively charged dust, and compressive solitons can exist for positively charged dust. The present study could be useful for the understanding of DASWs in various astrophysical environments.